Financing sustainable development? The role of foreign aid in Southeast Asia's energy transition. (5th August 2021) - Bertheau, Paul; Lindner, Robert
Abstract: The rapid deployment of modern renewable energy generation capacity in the fast‐growing Southeast Asian region will be crucial to ensure that the region can meet its increasing future energy demand in a sustainable way. However, many countries will need assistance through international cooperation and foreign aid to develop their sustainable energy sources. The three East Asian donor states Japan, South Korea and China are particularly crucial because they account for a large share of aid disbursement to the region and serve as development role models for many recipient countries. All three states are signatories of the Paris Agreement and the 2030 Agenda for Sustainable Development and thus committed to the global goals of climate protection and sustainable energy development. This paper is based on an analysis of official aid databases and second‐party data to explore the details of the energy‐related aid contributions of the three key donor states to Southeast Asia during the last 15 years. The findings indicate that all three states contradicted their own international pledges by financing fossil‐fuel power generation projects in many countries in the region. Although recent policy changes in Japan and South Korea are cause for optimism, the opacity of China's energy‐related aid flows combined with its renewed support for domestic coal power generation are worrying signs for the future of energy development in Southeast Asia and beyond.